Efektivitas Proses Pembelajaran Lembaga Kursus Komputer Aplikasi Perkantoran Melalui Penerapan Kurikulum Berbasis Kompetensi - Halimatusha’diah Halimatusha’diah (SAP (Susunan Artikel Pendidikan), 2018)
This study aims to determine the effectiveness of the learning process in institutions that organize courses in the field of computer office applications using a competency-based curriculum. This research was conducted by evaluating 8 institutions of course in Banten region with discrepancy model, that is by looking at the gap that happened in the process of learning conducted in the field. Data collection technique is by using questionnaire. The results of the evaluation show that in the learning process through the competency-based curriculum that includes the preparation of learning tools, the use of learning methods, the use of instructional media, and the implementation of the evaluation of learning, running effectively. While the implementation of internship programs with the business and industry has not run effectively.